The impact of BMI on long-term anthropometric and metabolic outcomes in girls with idiopathic central precocious puberty treated with GnRHas - Bruzzi, Patrizia; Valeri, Lara; Sandoni, Marcello; Madeo, Simona Filomena; Predieri, Barbara; Lucaccioni, Laura; Iughetti, Lorenzo (Frontiers in Endocrinology, 2022)
Background: Gonadotropin releasing hormone analogs (GnRHa) are effective in improving adult height in children with idiopathic central precocious puberty (ICPP). In last years, however, some transient metabolic complications have been described during the treatment without the reassurance of long-term data yet. The aim of our study is to evaluate the efficacy of GnRHa and to clarify if body mass index (BMI) at diagnosis of ICPP could influence long-term outcomes. Methods: This is an observational retrospective study recruiting a cohort of girls with ICPP. Anthropometric measures, fasting lipid profile and glucose metabolism were collected at baseline (when GnRHa started) [T1], at the end of the treatment [T2] and at near final height (nFH) or final height (FH) [T3]. Predicted adult height (PAH) was calculated at T1 according to Bayley and Pinneau’s method. Analysis was performed according to BMI-SDS categories at T1 (Group A: normal-weight vs. Group B: overweight/obese). Results: Fifty-seven girls with ICPP treated with GnRHa were enrolled (A vs. B: 33 vs. 24 patients, aged 7.86±0.81 vs. 7.06±1.61 years, p<0.05). In the study population, nFH/FH was in line with target height (TH) (p 0.54) with a mean absolute height-gain of 11.82±5.35 cm in comparison to PAH. Even if in group B, the length of therapy was shorter (1.84±2.15 vs. 2.10±0.81 years, p<0.05) and their age at menarche was earlier than in group A (10.56±1.01 vs. 11.44±0.85, p<0.05), the nFH/FH gain was comparable in the two groups (p 0.95). At nFH/FH, BMI-SDS was still greater in group B than in A (p 0.012), even if BMI-SDS significantly increased on GnRHa only in group A (p<0.05). Glucose metabolism got worst during GnRHa with a complete restoring after it, independently from pre-treatment BMI. LDL/HDL-C ratio transiently deteriorated during GnRHa only in group A (p 0.030). Conclusions: Our results confirm the efficacy of GnRHa on growth and do not support the concern that overweight and obesity could impair the long-term outcomes of GnRHa therapy. However, the observed transient impairment of metabolic parameters during treatment has to stimulate clinicians to encourage a healthy lifestyle in all ICPP girls treated with GnRHa, regardless their pre-treatment BMI.